Productive and reproductive performance of dairy cattle in Char areas of Bangladesh - Alam, MM; Sarder, MJU; Ferdousi, Z; Rahman, MM (Bangladesh Veterinarian, 2010)
Production traits of 60 indigenous (Desi), 20 Friesian × Desi and 20 Sahiwal × Desi cows were recorded in six char villages of Sariakandi upazila (Sub-district) of Bogra district. The mean (± SD) daily milk yields were 1.7 ± 0.6, 6.3 ± 1.2 and 5.1 ± 1.0 litres, respectively. The lactation lengths, ages at puberty, gestation lengths, calving intervals, numbers of services per conception, intervals between calving and first oestrus were 217.9 ± 18.7, 253.8 ± 21.9, 240.8 ± 15.7 days; 27.4 ± 2.7, 23.9 ± 2.0, 26.2 ± 2.4 months; 277.4 ± 4.2, 278.3 ± 4.2, 278.3 ± 4.0 days; 494.8 ± 27.3, 487.5 ± 17.4, 493.3 ± 16.2 days; 1.3 ± 0.5, 1.7 ± 0.6, 1.6 ± 0.5; 145.6 ± 27.4, 166.8 ± 33.0 and 170.5 ± 34.9 days, respectively. Daily milk yield and lactation length were significantly (p<0.01) better for cross-bred cows than for Desi, and age at puberty was significantly (p<0.01) better for Friesian-cross cows than for Desi, while number of services per pregnancy and onset of post partum oestrus were significantly (p<0.01) better for Desi than for cross-bred cows. There were no significant differences in gestation length and calving interval. It is suggested that the overall productive and reproductive performance of Friesian × Desi and Sahiwal × Desi cows were better than those of Desi cows. DOI: 10.3329/bvet.v25i2.4620 Bangl. vet. 2008. Vol. 25, No. 2, 68-74